An investigation of pain mechanisms in a model of osteoarthritis : modulation by the endocannabinoid receptor system - Staniaszek, Lydia Ewa (2010)
Osteoarthritis (OA) is expected to become the fourth leading cause of disability worldwide by 2020. There is no cure, and joint replacement surgery becomes a final resort. Chronic pain associated with OA is poorly controlled by current treatments, and often involve chronic use of non-steroidal anti-inflammatory drugs (NSAIDs), which is associated with serious side-effects. OA is associated with alterations in endocannabinoid (EC), an attractive target for the control of pain. ECs are rapidly degraded by a number of enzymes, including cyclooxygenase-2 (COX- 2), the major target of NSAIDs. However, the role of COX-2 in EC-mediated effects on nociceptive transmission is not fully understood. The aims of this thesis were to investigate peripheral and spinal pain responses in a model of OA pain, understand the role of COX-2 inhibition on neuronal responses and the potential role of ECs in mediating these effects, and to establish the functional effects of the EC system in a model of OA pain. Effects of spinal and peripheral administration of the COX-2 inhibitor nimesulide (1-1 OOlJgin 501JL)on mechanically evoked responses of dorsal horn neurones in the naive, anaesthetised rat were measured, and the contribution of the CB1 receptor was determined with the antagonist AM251 (11Jgin 50IJL). Effects of nimesulide on spinal levels of ECs and related compounds were quantified using liquid chromatography-tandem mass spectrometry. Spinal, but not peripheral, injection of nimesulide significantly reduced mechanically evoked responses of dorsal horn neurones. Inhibitory effects of spinal nimesulide were blocked by the CB1 receptor antagonist AM251, but spinal EC levels were not elevated. Indeed, both anandamide and N-oleoylethanolamide were significantly decreased by nimesulide, highlighting a putative role for other oxidative enzymes of ECs in the generation of CB1-active metabolites. The monosodium-iodoacetate (MIA) model of OA pain has recently received much interest, but is not yet fully defined. Work in this thesis sought to further characterise this model. Cytokine levels in synovial fluid, spinal cord and hindpaw skin at early time-points post- intra-articular injection (1mg MIA in 50IJL, P.O. 3-24hr) were measured, and the later (P.O. day 28-31) effects on neuronal responses and pain behaviour were determined. Intra-articular injection of 1mg MIA produced stable and robust changes in two measures of pain relevant to clinical OA, and evidence for the presence of central sensitisation was demonstrated. It was also demonstrated that early-stage painful responses in this model are not associated with changes in cytokines in the joint. Effects of spinal and systemic administration of nimesulide (3-100IJg in 501JL)on mechanically evoked and post-stimulus responses of dorsal horn neurones in MIA-treated rats were also measured, as were the effects of spinal cannabinoid receptor antagonism with AM251 (0.1- 10IJg in 501JL)and the CB2 receptor antagonist SR144528 (0.001-0.1IJg in 50IJL). Spinal and systemic COX-2 inhibition in the MIA model attenuated spinal neuronal responses to both noxious and innocuous stimuli, demonstrating the importance of both spinal and peripheral COX-2 products in mediating neuronal responses in this model. Antagonism of the spinal cannabinoid receptors resulted in elevated spinal neuronal responses in MIA-treated rats, demonstrating a functional role for spinal EC-mediated modulation of nociceptive transmission in the MIA model, expanding on work in this lab which showed elevated spinal ECs in the MIA model of OA pain. This work therefore demonstrates that the central EC system may be an important target for the treatment of OA pain.